Analysis of protective plate in manifold drop object protection structure - Yuan, Quan. (2012)
The primary roof body of a subsea manifold dropped object protection structure consists of protective plates, welded at each edge, arranged in a suitable pattern to protect various components within a manifold from any external damage. The protective plates should be able to absorb impact caused by accidental dropped loads.